Exercise of the leadership and effectiveness of educational management. primary public institutions - Trujillo-Atapoma, Pio (2019)
The objective of the present investigation was to determine the relationship between the exercise of the leadership of the directors and the effectiveness of the management of the Public Educational Institutions of the Primary Level of Huanuco, during 2018. It was a study with a quantitative approach, of a correlational type, Prospective and transversal. The sample was made up of 79 teachers, selected by probabilistic sampling. A scale of effectiveness of the educational management and of evaluation of the leadership exercise, previously validated and reliable, were applied with prior informed consent. The descriptive analysis was performed and in the inferential Pearson's r test was used. In the results it was observed that there was a significant correlation between the dimensions: teamwork and effectiveness of educational management (r = 0.754); institutional climate and effectiveness of educational management (r = 0.765); decision making and effectiveness of educational management (r = 0.710); teaching performance and effectiveness of educational management (r = 0.641), with p ≤ 0.000. It is concluded that there is a significant correlation between the exercise of managerial leadership and the effectiveness of educational management (r = 0.773 and p = 0.000), in the UGEL Huanuco during 2018.